(3GdCSS GdYdejI defGgL GdHMK GdELJeGYj (B/s - (3GdMSf, EMSGf eMeOs ((3HjQhJ (B:s (3OGQ GdWdjYI ddWHGYI h GdfTQ ,s, 1982)
(3jMJhj GdcJGH Ydi (B12 (3aUdG jSJhYH ajgG GdbGQF LejY efGgL GdHMK GdGLJeGYj h afhfg h GSGdjHg GdYdejI h GdeTcdGJ GdefgLjI s
Keywords: (3GdHMK GdYdejs; (3efGgL GdHMK GdELJeGYjs